Market concentration in Europe: Evidence from antitrust markets - Pauline Luise Affeldt; Tomaso Duso; Klaus Gugler; Joanna Piechucka (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
An increasing body of empirical evidence is documenting trends toward rising concentration, profits, and markups in many industries around the world since the 1980s. Two major criticisms of these studies is that concentration and market shares are poorly measured at the national industry level while firm level revenues are a poor indicator of product sales. We use a novel database that identifies over 20,000 product/geographic antitrust markets affected by over2,000 mergers scrutinized by the European Commission between 1995 and 2014. We show that concentration, as measured by the market-specific post-merger HHI, is larger than reported in the extant literature (at least) by a factor of ten. We also show that concentration has increased over time on average. Yet, there is a great deal of heterogeneity across geographic markets and within broader industries. In a regression analysis that exploits this within-industry variation, we show that barriers to entry are unambiguously positively related to concentration irrespective of time periods, sectors of activity, and geographical market dimension analyzed. Strict past merger enforcement negatively correlates with concentration. Yet, this effect is stronger in the earlier decade (1995-2004) than subsequently. Intangibility of investments consistently displays positive correlation with concentration only for EU wide and worldwide services markets. In contrast, the correlation is negative in national markets. This underscores the importance of the large heterogeneity present in concentration developments across markets.
Keywords: L24; L44; K21; O32; 330; Concentration; HHI; Market Definition; Entry Barriers; Mergers; Merger Control; Intangibles